A review of Kenya's cancer policies to improve access to cancer testing and treatment in the country - Louise Kathini Makau-Barasa; Sandra Greene; N. A. Othieno-Abinya; Stephanie B. Wheeler; Asheley Skinner; Antonia V. Bennett (BMC, 2020)
Abstract Background Cancer is the third-leading cause of mortality in Kenya, resulting in unique challenges to the country's health system. An increase in the number of cancer cases in Kenya over the past decade resulted in legislative actions and policies to guide delivery of cancer services. Kenya's new national cancer control strategy and past policy efforts provide an opportunity to synergise information and enhance understanding to improve cancer diagnosis and treatment in the country. The objectives of this study are to (1) document policy-modifiable factors based on a review of policy documents and results of a key informant survey and (2) develop recommendations to improve policies affecting cancer testing and treatment services in Kenya. This study builds upon our previous study Improving Access to Cancer Testing and Treatment in Kenya (Makau Barasa et al. J Global Oncol 2(216), 2017). Methods The study applied an in-depth systematic review of Kenya's cancer policies and guidelines, a qualitative analysis of results from a section of a semi-structured key informant survey focused on the opinions of clinicians delivering cancer services as well as cancer support groups and advocacy leaders, and a stakeholder analysis identifying key policy-makers and implementers. Details of the complete key informant survey were published in our previous study. Results Kenya's cancer policies have guided progress made in providing the legal and implementation frameworks for the development and delivery of cancer services at the national and county levels. Some policy implementation gaps are noted. These include inadequate financing for cancer services, limited research and data to support policy formulation, and the concentration of cancer services in urban areas. The key informant survey identified policy-modifiable actions that can address some of the gaps and improve the delivery of and access to cancer testing and treatment services in the country. Some of these include addressing the financial barriers affecting cancer testing and treatment services; increasing stakeholder engagement in training health personnel to deliver cancer testing and treatment services; decentralising cancer services and improving cancer surveillance and research; and increasing education and awareness about cancer symptoms, screening procedures and treatment options. A set of priority policy actions were selected from the study findings and used to develop recommendations for Kenya's policy-makers and stakeholders. Conclusions Revisions to Kenya's cancer policies are seeking to address gaps noted in past policies and to improve access to cancer testing and treatment in Kenya. However, based on study findings, additional actions can be taken to strengthen policy implementation. Considering the policy formulation and implementation process and costs, this study recommends focusing on three priority policy actions that can have significant impact on improving access to cancer testing and treatment services. These include addressing financing, insurance and human resources gaps; increasing stakeholder engagement; and decentralising health services for better surveillance and data to inform policies.